Acute acalculous cholecystitis and gall bladder perforation induced by Salmonella enterica serovar typhi - Khatri, N.S.; Koirala, S.; Aryal, A.; Maskay, P.; Paudel, S.; Karkey, A.; Baker, S.; Shilpakar, O; Shrestha, K.; Basnet, B. (Journal of Institute of Medicine Nepal, 2009)
Salmonella Typhi is a causative agent of enteric fever, which is an ongoing public health problem in urban areas of the Kathmandu valley in Nepal. It is estimated that approximately 5 % of people in an endemic enteric fever area may asymptomatically carry Salmonella Typhi in the gall bladder. Here we describe a rare clinical manifestation of chronic Salmonella carriage. A 40 year old male resident of Kathmandu underwent an emergency cholecystectomy for acute cholecystitis and gall bladder perforation. No stone was identified but Salmonella Typhi was cultured from the gall bladder